Less is more: Antibiotics at the beginning of life - Stocker, Martin; Klingenberg, Claus; Navér, Lars; Nordberg, Viveka; Berardi, Alberto; El Helou, Salhab; Fusch, Gerhard; Bliss, Joseph M; Lehnick, Dirk; Dimopoulou, Varvara; Guerina, Nicholas; Seliga-Siwecka, Joanna; et al. (Nature communications, 2023)
Antibiotic exposure at the beginning of life can lead to increased antimicrobial resistance and perturbations of the developing microbiome. Early-life microbiome disruption increases the risks of developing chronic diseases later in life. Fear of missing evolving neonatal sepsis is the key driver for antibiotic overtreatment early in life. Bias (a systemic deviation towards overtreatment) and noise (a random scatter) affect the decision-making process. In this perspective, we advocate for a factual approach quantifying the burden of treatment in relation to the burden of disease balancing antimicrobial stewardship and effective sepsis management.
Keywords: novorozenec; Infant, Newborn; Neonatal Sepsis; novorozenecká sepse; počátek lidského života; sepse; Humans; Antimicrobial Stewardship; Anti-Bacterial Agents; lidé; antibakteriální látky; antibiotická politika; Sepsis; Beginning of Human Life